2021
DOI: 10.7759/cureus.16855
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamins in Non-Alcoholic Fatty Liver Disease: A Systematic Review

Abstract: Non-Alcoholic Fatty Liver Disease (NAFLD) emerged as the most prevalent liver disorder contributing significantly to disease burden worldwide. It manifests as a broad spectrum of hepatic damage with varying severity ranging from less serious steatosis to a more severe Non-Alcoholic Steatohepatitis (NASH), with or without fibrosis, cirrhosis, and hepatocellular carcinoma. Vitamins, on the other hand, are micronutrients that are vital for healthy well-being. Some studies have linked liver diseases with hypovitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
(175 reference statements)
1
26
0
Order By: Relevance
“…In addition to enhancing fatty acid synthesis, folate deficiency also decreases the methylation and thus the formation of phosphatidylcholine, leading to less very low-density lipoprotein produced for hepatic lipid efflux ( 25 ). Therefore, an increasing number of evidence suggested the association between folate status with non-alcoholic fatty liver disease in the recent review articles ( 35 , 36 ). In our study, folate-deficient mice also had more steatosis, hepatocytes ballooning, and lobular inflammation, suggesting that chronic lipid accumulation enhanced by folate deficiency might result in pathological changes in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enhancing fatty acid synthesis, folate deficiency also decreases the methylation and thus the formation of phosphatidylcholine, leading to less very low-density lipoprotein produced for hepatic lipid efflux ( 25 ). Therefore, an increasing number of evidence suggested the association between folate status with non-alcoholic fatty liver disease in the recent review articles ( 35 , 36 ). In our study, folate-deficient mice also had more steatosis, hepatocytes ballooning, and lobular inflammation, suggesting that chronic lipid accumulation enhanced by folate deficiency might result in pathological changes in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is strictly associated with obesity and higher glycated levels [ 61 , 62 ], with lower levels of folate and vitamin B12 [ 63 , 64 ], and a reduction in folate level [ 65 ]. More recently, NAFLD has been associated with higher levels of homocysteine [ 66 ] and most probably hypovitaminosis D [ 13 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A, vitamin B 3 , folic acid, vitamin C, and vitamin D have all been studied in the context of NAFLD, but these studies fail to provide any conclusive evidence on the routine administration of such micronutrients for the management of NAFLD. 35 However, among the micronutrients, vitamin E is the most validated to treat patients with NAFLD. The PIVENS (Pioglitazone, Vitamin E or Placebo for the Treatment of Nondiabetic Patients with Nonalcoholic Steatohepatitis) trial showed that 800 IU of vitamin E daily was associated with improvement in transaminases and histologic steatosis and inflammation.…”
Section: Role Of Micronutrients and Other Nutritional Therapy In Nafldmentioning
confidence: 99%